Change in Knowledge, Attitude and Practice Regarding Anaemia among High School Girls in Rural Bangalore: An Health Educational Interventional Study - Talakad Shesha Iyengar Chaluvaraj; Pradeep Tarikere Satyanarayana (Medsci Publications, 2018)
Background: Adolescent girls are particularly vulnerable to ane- mia compared.KAP assessment is suitable to evaluate the effec- tiveness of intervention programs. This study was carried out to assess the knowledge, attitude and practice regarding anemia and improvement in same after health education among high school girls in rural Bangalore. Materials and Methods: It's a cross sectional interventional study. All girls were included age group 14 to 16 years and those who did not consent were excluded from the study which was carried out  in Govt High School in Hoskote, Rural Bangalore for a period of three months. All the data were entered in Microsoft excel and analyzed using SPSS v 22. Results: Among 100 study participants, 78 % belonged to age group of 13-14 years, 85% belonged to nuclear family. Initial as- sessment showed Knowledge being poor, Attitude being negative and practice being unsatisfactory and health education were given through various forms. Conclusion: The overall findings of the study showed the know- ledge, attitude and practices of female adolescents are moving in a desirable direction post health education. Comprehensive nutri- tional education regarding anemia and consequences among ado- lescents can yield a great dividend in future life of women.